KAJIAN KANDUNGAN GARAM DAN TEMPERATUR TERHADAP TEGANGAN TEMBUS MINYAK ISOLASI - purwiyanto, purwiyanto (Universitas Lampung, 2024)
To avoid the occurrence of currents, jumps or electric sparks between electrical conductors, then isolation is used. Insulating oil is one of the insulating materials used in transformers that function to isolate and cool electrical equipment. The properties of transformer insulating oil change when it contains pollutants that enter the oil, in which causes faster failure. Besides the change of temperature will also affect the strength of the insulating oil. The results showed that the percentage contribution of the effect of temperature and salt content on the breakdown voltage was 36.4% with a temperature increase of 10C followed by an increase in the breakdown voltage of 0.044 times and each increase in the salt content was followed by a decrease in the breakdown voltage of 0.292 times.